Pholosophizing on educational matters - Orteza Evelina Miranda
The purpose of this study is to describe briefly what is commonly said to be an academic or theoretical research. This is a broader category which could include qualitative and qualitative research. The next purpose is to do philosophy, as distinguished from talking and knowing about it, on some educational matters and to describe it in parts.
This paper was read at the College of Education, University of the Philippines, 21 February 1990.
Keywords: Education -- Philosophy